Formation of creative abilities of schoolboy's by means of new musical computer programs - N.А. Ovcharenko (Academy of Cognitive and Natural Sciences, 2006)
The nature of concept "of creative capacities" is uncovered the ways of their formation for the schoolboys at lessons of music are esteemed in this article. The modem approach in realization of lessons of music with usage of new computer programs is offered.